2016
DOI: 10.14254/2071-789x.2016/9-4/4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Institutions for Knowledge-based Economy within New Institutional Economics Framework. Multiple Criteria Decision Analysis for European Countries in the Years 2000–2013

Abstract: The article concentrates on the problem of quality of institutions in the European Union countries in the context of their compatibility with the global knowledge-based economy. The main objective of the article is to evaluate the progress obtained in that field by New Member States of the European Union in the years 2000-2013. The empirical research is based on the following hypothesis: the integration process of Central European countries with the European Union has influenced the acceleration of changes lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 27 publications
2
47
0
1
Order By: Relevance
“…The procedure for obtaining TMD can be given in the following steps (Balcerzak, 2016;2017;Balcerzak and Pietrzak, 2016e):…”
Section: Taxonomic Measure Of Development Proposed By Hellwigmentioning
confidence: 99%
“…The procedure for obtaining TMD can be given in the following steps (Balcerzak, 2016;2017;Balcerzak and Pietrzak, 2016e):…”
Section: Taxonomic Measure Of Development Proposed By Hellwigmentioning
confidence: 99%
“…Examples of measuring institutions, as well as operations over institutions, meaning calculus of institutions, are given in (Makarov, 2003;Balcerzak and Pietrzak;Żelazny and Pietrucha, 2017). Issues of measuring the impact of institutions on the economic system with examples of direct and indirect institutional gauges are considered in (Shuaibu and Oladayo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The stronger is the sociocultural agreement, then the more certain is that livelihood strategy should fulfill household needs. [14] used Institutional Economic Theory to explain the role of knowledge in the change of European economic after the integration of European countries into European Union. Consistent to this statement, [15] has concluded that participation as the important aspect in social capital is very determining to organizational quality.…”
Section: Economic Sociology Approach Inmentioning
confidence: 99%